Draft Annual Plan 1987-88 the Twenty-Point Programme 1986 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1987)
The 20-Point Programme introduced in January 1982 contains various salient points. This Union Territory Administration have taken effective steps to implement all the related points under the 20-Point Programme so as to give various benefits to the poorest of the poor and to the vulnerable groups.
Government of Pondicherry, Planning and Research Department